Diversity, Distribution and Abundance of Scleractinian Coral in District-based Marine Protected Area Olele, Bone Bolango, Gorontalo - Indonesia - Reza, Akbar; Peni Sancayaningsih, Retno (KnE Life Sciences, 2017)
Despite its status as District-Based Marine Protected Area, studies pertaining coral reef biodiversity never been conducted in Olele that located in the Gulf of Tomini, biodiversity hotspot in the Coral Triangle. Hence, we aims to investigate diversity, distribution and abundance of scleractinian coral, underpinning the health of reef ecosystems. This study was conducted using Line Intercept Transect on three research stations which were divided into three main zonations, reef flat (3 m depth), upper reef slope (10 m depth) and reef slope (18 m to 20 m depth). Fifty meters long transect were laid in each zonation, thus total transect were nine. The results showed that there were 35 species of scleractinian coral from 12 families. Each zonation has a different pattern of abundance and dominant life form. Based on coral health assessment using Coral Mortality Index (CMI) and the ratio between living and dead coral coverage, coral reef ecosystems in Olele were in healthy condition with the range value 0.29 ± 0.1 and 3.60 ± 1.14. This preliminary study should be used as a basic reference for database and novel direction of conservation management strategy in District-Based Marine Protected Area Olele. Keywords: district-based marine protected area; olele; lit; sclecartinia;life form; zonation.